Software technologies : 12th International Joint Conference, ICSOFT 2017, Madrid, Spain, July 24-26, 2017, Revised selected papers /: 12th International Joint Conference, ICSOFT 2017, Madrid, Spain, July 24-26, 2017, Revised selected papers. (2018) - Unknown
No abstract available